Harvesting indoor available light for low-power wireless networks - Caldeira, A.; Almeida, A. (6th International Conference on Wireless Networks and Mobile Communications, 2018)
Currently wireless networks used in indoor environments use the power grid as their main power source. In the particular case of sensor networks, the use of batteries is more common. Batteries, however, have a limited lifetime and have to be replaced regularly. Both the life-span and the cost of replacing the batteries are factors limiting the system where these batteries are used. On the other hand, also from the environmental point of view, it is important to minimize the waste generated by end-of-life batteries. In spite of the technological advances, which in the last decade have increased the energy efficiency of the batteries, it would be of interest (with a relevant social impact) if we could extend the lifetime of a device by the collection and re-use of the energy present in the environment. In particular, the electric energy spent on indoor lighting, whether homes or offices, can be partially recovered by harvest devices like photovoltaic cells. In this paper we explore the possibility of powering sensor nodes exploiting the energy that can be recovered from the existing room light.